Moringa Oleifera In the Form of Ready Useable Food Therapy as Stunting Preventer - Waifti Amalia (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2025)
The prevalence of malnutrition which can result in stunting is still a serious problem in Indonesia. Until now, research is still continuing on the most effective prevention of this problem. The large number of supplements circulating with a mixture of chemicals can often cause health problems in the future. Moringa oleifera (moringa leaves) can be an alternative to prevent stunting problems. People still use this plant as an accompaniment to everyday cooking, and it is not uncommon for this plant to only be used as decoration in their yard. From the results of a preliminary study at Pandanmulyo Community Health Center, Pandanmulyo Village, it was found that there were 21 cases of malnutrition and 23 cases of children experiencing malnutrition. Researching whether or not Moringa leaves may help malnourished youngsters gain weight is the driving force for this project. Using a non-randomized pretest-posttest control group design, this study applies quantitative research approaches. The sample was 20 toddlers aged 1-3 years old. Paired t-test analysis was used to determine the comparison of weight between groups. From the research results, data was obtained that there was a significant difference in the control group and the treatment group with a p value of 0.037 (p <0.05) which shows that giving Moringa aloifera in the form of Ready Useable Therapy Food for 4 weeks can increase the weight of toddlers.